2012
DOI: 10.1016/j.seizure.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Four types of traditional Chinese medicine inducing epileptic seizures

Abstract: Traditional Chinese medicine has been used to treat disease in China for more than five thousand years. Over the last few decades it has been used increasingly in other countries as well. As its use has spread, interest in the adverse effects of traditional Chinese medicine, including epilepsy and epileptic seizures, has grown. To date, four types of traditional Chinese medicine have been found to induce epileptic seizures. In this review we will summarize the current knowledge about possible epileptogenic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…In modern times, industrial-scale production has developed with less rigorous quality control, and MPs have been regulated as food or food supplements or have been imported for use without regulation. Some WMPs have been associated with repeated, severe adverse reactions, including liver and kidney toxicity (sometimes fatal) [8688], heavy metal poisoning [8993], epileptic seizures [94], and adrenal suppression from undeclared addition of corticosteroids to herbal products [90]. There are further concerns regarding environmental contaminations (e.g., air pollution, soil contaminations), cultivation practices (e.g., pesticides, fungicides, microorganisms, endotoxins), manufacturing procedures (e.g., microorganisms, endotoxins), and inappropriate use [95, 96].…”
Section: Resultsmentioning
confidence: 99%
“…In modern times, industrial-scale production has developed with less rigorous quality control, and MPs have been regulated as food or food supplements or have been imported for use without regulation. Some WMPs have been associated with repeated, severe adverse reactions, including liver and kidney toxicity (sometimes fatal) [8688], heavy metal poisoning [8993], epileptic seizures [94], and adrenal suppression from undeclared addition of corticosteroids to herbal products [90]. There are further concerns regarding environmental contaminations (e.g., air pollution, soil contaminations), cultivation practices (e.g., pesticides, fungicides, microorganisms, endotoxins), manufacturing procedures (e.g., microorganisms, endotoxins), and inappropriate use [95, 96].…”
Section: Resultsmentioning
confidence: 99%
“…Ancak, beşbin yıldan daha fazla bir zamandan beri bitkisel kökenli ilaçlar epilepside kullanıl-maktadır. [15,16] Çalışmaya katılanların nöbet esnasındaki uygulamaları arasında, hastayı yan yatırma, ayakları yukarı kaldırma, yumuşak bir yere yatırmaya ek olarak dişler kilitlendiğinde arasına kaşık, havlu sokma bulunmaktaydı. Sidig ve ark.…”
Section: Discussionunclassified
“…16 Da higher than that of strychnine, which indicated that they were isomers of hydroxylation or oxidation products of strychnine. + ) and similar dominant fragment ions, indicating that they were isomers.…”
Section: Tentative Identication Of the Sas Extractmentioning
confidence: 91%
“…A2 was conrmed as strychnine by comparing the retention time and MS 2 fragment ions with the authentic standard. In addition, the cleavage of the bonds between C 7 and C 17 , C 16 and C 19 , C 20 and C 21 generated the major fragment ion at m/z 306.11203 and described the position of the hydroxyl group only to be C 16 . Therefore, A1 was tentatively identied to be isostrychnine according to its accurate molecular mass and structural characteristic.…”
Section: Tentative Identication Of the Sas Extractmentioning
confidence: 99%